Monetary policy, central banks and economic performance in the Caribbean - Boyd, Derick (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Analyzes how monetary policy performed in a sample of Caribbean countries and examines the question of the benefits of a single currency institutional framework.